Cytomegalovirus prevention strategies and the risk of BK polyomavirus viremia and nephropathy - Reischig, Tomas; Kacer, Martin; Hes, Ondrej; Machova, Jana; Nemcova, Jana; Lysak, Daniel; Jindra, Pavel; Pivovarcikova, Kristyna; Kormunda, Stanislav; Bouda, Mirko (American journal of transplantation, 2019)
Polyomavirus BK (BKV) is the cause of polyomavirus-associated nephropathy resulting in premature graft loss. There are limited data regarding the role of cytomegalovirus (CMV) infection and its prevention in developing BKV viremia and PVAN. In a prospective study, we analyzed 207 consecutive renal transplant recipients previously enrolled in 2 randomized trials evaluating different CMV prevention regimens with routine screening for BKV and CMV. Of these, 59 received valganciclovir and 100 valacyclovir prophylaxis; 48 patients were managed by preemptive therapy. At 3 years, the incidence of BKV viremia and PVAN was 28% and 5%, respectively. CMV DNAemia developed in 55% and CMV disease in 6%. Both BKV viremia (42% vs 23% vs 21%, P = .006) and PVAN (12% vs 2% vs 2%, P = .011) were increased in patients treated with valganciclovir prophylaxis compared to valacyclovir and preemptive therapy. Using multivariate Cox proportional hazard regression, valganciclovir prophylaxis was independent predictor of BKV viremia (hazard ratio [HR] = 2.38, P = .002) and PVAN (HR = 4.73, P = .026). In contrast, the risk of subsequent BKV viremia was lower in patients with antecedent CMV DNAemia (HR = 0.50, P = .018). These data suggest valganciclovir prophylaxis may be associated with increased risk of BKV viremia and PVAN. CMV DNAemia did not represent a risk for BKV.
Keywords: Male; infectious disease; Cytomegalovirus; Treatment Outcome; lidé středního věku; valaciclovir; kidney transplantation/nephrology; Prospective Studies; Kidney Transplantation; Graft Survival; transplantace ledvin; Humans; polyomavirové infekce; Valganciclovir; Middle Aged; premedikace; randomizované kontrolované studie jako téma; rizikové faktory; Valacyclovir; prospektivní studie; infection and infectious agents - viral: cytomegalovirus (CMV); mužské pohlaví; Cytomegalovirus Infections; Female; Premedication; chronické selhání ledvin; virus BK; clinical trial; Randomized Controlled Trials as Topic; Tumor Virus Infections; valganciklovir; ženské pohlaví; Proportional Hazards Models; infekce onkogenními viry; Adult; BK Virus; proporcionální rizikové modely; Viremia; viremie; multivariační analýza; Polyomavirus Infections; clinical research/practice; přežívání štěpu; infection and infectious agents - viral: BK/JC/polyoma; dospělí; cytomegalovirové infekce; lidé; Multivariate Analysis; Kidney Failure, Chronic; Risk Factors; výsledek terapie